Adipocyte ACLY Facilitates Dietary Carbohydrate Handling to Maintain Metabolic Homeostasis in Females - Sully Fernandez; John M. Viola; AnnMarie Torres; Martina Wallace; Sophie Trefely; Steven Zhao; Hayley C. Affronti; Jivani M. Gengatharan; David A. Guertin; Nathaniel W. Snyder; Christian M. Metallo; Kathryn E. Wellen (Cell Reports, 2019)
Summary: Sugars and refined carbohydrates are major components of the modern diet. ATP-citrate lyase (ACLY) is upregulated in adipocytes in response to carbohydrate consumption and generates acetyl-coenzyme A (CoA) for both lipid synthesis and acetylation reactions. Here, we investigate the role of ACLY in the metabolic and transcriptional responses to carbohydrates in adipocytes and unexpectedly uncover a sexually dimorphic function in maintaining systemic metabolic homeostasis. When fed a high-sucrose diet, AclyFAT−/− females exhibit a lipodystrophy-like phenotype, with minimal fat accumulation, insulin resistance, and hepatic lipid accumulation, whereas AclyFAT−/− males have only mild metabolic phenotypes. We find that ACLY is crucial for nutrient-dependent carbohydrate response element-binding protein (ChREBP) activation in adipocytes and plays a key role, particularly in females, in the storage of newly synthesized fatty acids in adipose tissue. The data indicate that adipocyte ACLY is important in females for the systemic handling of dietary carbohydrates and for the preservation of metabolic homeostasis. : Sugar is a major component of the modern diet. Fernandez et al. identify ATP-citrate lyase (ACLY) as a key facilitator of transcriptional and metabolic responses to dietary carbohydrates in adipocytes. Lack of adipocyte ACLY disrupts proper storage of lipids in adipose versus liver and promotes insulin resistance, particularly in females. Keywords: acetyl-CoA, ATP-citrate lyase, adipocyte, adipose tissue, liver, sexual dimorphism, carbohydrate, glucose, fatty acid synthesis, ChREBP